Descriptions, transference and new records of Lamiinae from Central and South America (Coleoptera, Cerambycidae) - Santos-Silva, Antonio; Bezark, Larry G.; Galileo, Maria Helena M.; Li, Lin (Zootaxa, 2016)
Two new species are described in Calliini: Callisema jirouxi sp. nov. from Ecuador and Colombicallia setosa sp. nov. from Costa Rica. Keys to species of Callisema and Colombicallia are provided. Psapharochrus alboguttatus (Melzer, 1935) is transferred to Alphus White, 1855. New country, department and state records are provided in Lamiinae.